KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MATERI BARISAN DAN DERET ARITMATIKA DI KELAS XI SMK - Hastari, Nana; Sugiatno, Sugiatno; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research to describe studentâ€™s mathematical connection ability in sequence and arithmetic series material. The reseach method used is descriptive with research form of survey. Subjects involved in this study were students in grade XI SMK Boedi Oetomo with the research object is students mathematical connection ability in sequence and arithmetic series. The results of this research in shows that students mathematical connection ability in sequence and arithmetic series material which is associated with the context of the production of moderate category of goods (question number 1) with average values 70 and of very low category (question number 2) with average values 20. While the students mathematical connection ability in sequence and arithmetic series materialwhich is associated with the context of the production of a very low category of goods with an overall score of 37. Overall it can be concluded that students mathematical connection ability in sequence and arithmetic series material classified as very low with average values 42.Â Keyword: Mathematical Connection Ability, Sequence and Arithmetic Series